Towards understanding the ecology and mechanisms of biocontrol of Clonostachys rosea IK726 - Mette Lübeck; Inge M B Knudsen; Birgit Jensen; Mojtaba Mamarabadi; Dan Funck Jensen (浙江大学学报. 农业与生命科学版)
Clonostachys rosea (syn. Gliocladium roseum) IK726 was originally selected as an effective biocontrol agent (BCA) against cereal seed borne diseases caused by Fusarium culmorum and Bipolaris sorokiniana. We have studied the efficacy of the antagonist against different pathogens in several crops and found that the antagonist also is able to control Alternaria radicina and A. dauci on carrot seeds and different cold-storage fungi in acorns. IK726 is also able to reduce severity of soil borne Pythium spp. in cabbage, carrot and sugar beet. In addition, growth-promoting effects of IK726 have been demonstrated in barley and tomato. In order to develop and improve application methods and control strategies, essential basic studies of ecology and the mechanisms of control of IK726 is needed and has led us to use various molecular tools. The UP-PCR technology is used for strain recognition and we have developed GUS and GFP-transformants that resembles the wildtype strain in ecological fitness parameters. Using either the GUS-transformant or UP-PCR we have found that IK726, when applied with seeds, reproduces and survives several months in the rhizosphere of field grown barley and carrot. The GFP-transformant is used to study the behavior and in situ interactions of the antagonist with pathogens and plants. Using the GFP marker, we have observed conidial germination, colonization and conidiogenesis in natural soil, in vermiculite and on carrot and barley seed and roots and on barley leaves. Moreover in situ interactions with Alternaria on carrot material have been studied. The modes of action of C. rosea are not well understood but enzymatic activity, mycoparasitism, substrate competition, antibiosis and induced resistance are thought to play a role. Barley treated with C. rosea IK726 has an enhanced chitinolytic and glucanolytic activity compared to the activity in non-treated barley in pot experiments with field soil. Identification of chitinases from IK726 and studies of their role in interactions with pathogens have therefore been addressed in a recently initiated project. Preliminary results indicate that IK726 produces three types of chitinases, which seem to be regulated by glucose. Development of degenerated primers for cloning of an endochitinase is in progress.